(untitled) (Saúde Ética & Justiça, 2009)
Mass Disasters have always occurred and now with more frequency by the action of man. Thus, we consider important the inclusion of this topic, both by the multidisciplinary aspect of the work that follows thedisasters, in which professionals from fields of health, justice and civil defense are involved, as well as to be of interest of the whole society. The scope of this paper is to present some of the main mass disasters in recent years published in the literature focusing on the issues in which professionals in these situations are involved, as well as the scientific advances and their significance for human identification. We present: a) the difficulties found in identifying victims of the terrorist attacks of September 11, 2001 at the World Trade Center; b) the use of techniques for identifying victims of wars, genocides; c) the use of techniques for identifying victims of natural disasters, as the tsunami in South Asia on December 26, 2004; d) the identification of the responsible of a mass disaster, in a bombing in Jakarta in 2004 and e) the Internet as a tool for monitoring the health in Georgia in Victims of Hurricane Katrina, occurred on August 29, 2005, and the event consequences. As the final consideration we present some recommendations, described after experiences in occurred events.